Tourism Village Management Based on Local Community Participation in Kemiren Village, Glagah District, Banyuwangi Regency: Tata Kelola Desa Wisata Berbasis Partisipasi Masyarakat Lokal Di Desa Kemiren Kecamatan Glagah Kabupaten Banyuwangi - Dwi Fitriyani; Leni Vitasari; Erna Agustina (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Kemiren Village was designated as a tourist village by the Banyuwangi Regency government. This is in accordance with the Decree of the Head of Kemiren Village, Glagah District, Banyuwangi Regency regarding the designation of Kemiren Village as a tourist village. With unique traditions and culture, Kemiren Village is able to attract tourists to learn and get to know local culture. With culture inherent in the lives of local people, Kemiren Village is an attraction for tourists. The method used is based on qualitative escriptive principles. Primary data comes from interviews, and secondary data comes from literature reviews and various regulations relevant to the substance of the research. The result, in the management of tourist villages, participation from the local community is very necessary. The tourism governance implemented by POKDARWIS heavily involves the direct role of the community. This is supported by a tourism management system based on community based tourism where the local community is the main driver in tourism activities in Kemiren Village. Community participation is one of the principles of sustainable tourism development so that community involvement in the planning, development, management and evaluation processes of tourism development programs